Antihistamines: Beyond just allergy treatment - Hue T. H. Bui; Xuan-Hung Nguyen (Vietnam Journal of Science, Technology and Engineering)
Histamine and its receptors (H1R-H4R) are involved in several significant physiological processes and pathogenic conditions. Antihistamines, widely recognised as drugs for treating allergies, belong to the H1 antihistamine group, which targets H1R on endothelial cells, smooth muscle cells, and immune cells to alleviate allergic symptoms. Less well-known are H2 antihistamines and H3 antihistamines, which have been developed and approved for treating gastric acid diseases and narcolepsy, respectively. Preclinical and clinical studies have demonstrated the efficacy of numerous H1 and H2 antihistamines, which have been approved for clinical use with specific indications, in addressing viral infectious diseases, cancer, and multiple sclerosis. The low prices and established safety profiles of these antihistamines over the past decades position them as promising candidates for addressing these conditions, which still lack effective and affordable treatments. Accelerating clinical trials and licensing procedures is essential to introduce antihistamines with their novel applications to the market. This review emphasises the critical roles of histamine and its receptors in various biological processes, discusses the current clinical uses of antihistamines, and explores repurposing antihistamines for novel medical indications.